Evaluaciones de cultivares comerciales de pastos en Izabal, Guatemala - Mena Urbina, Martin A.; Hernandez Quevedo, Monica; van Der Hoek, Rein; Navarro Racines, Carlos (2023)
The CGIAR initiative on Livestock, Climate, and System Resilience (LCSR), later abbreviated as Livestock and Climate, addresses the complex challenges facing livestock systems in the context of climate change. Guatemala was identified as a priority country for the initiative's initial implementation cycle (2022-2024). As part of WP1, this report outlies the 2023 progress of a forage experiment in the department of Izabal including the Asociación de Ganaderos de Izabal (AGI), the Centro Universitario de Izabal (CUNIZAB) of the University of San Carlos and the Alliance of Bioversity International and CIAT. The objective of the trial is to assess the adaptability, productivity, and nutritional quality of commercial grass accessions under the prevailing climate and soil conditions in Izabal, incorporating appropriate grazing management practices. The trial consists of two parts, each at a different site: 1. well-drained soils with five forage accessions: Urochloa brizantha cv Toledo, Urochloa híbrido “Mulato”, Urochloa híbrido “Caymán”, Megathyrsus maximus cv. Mombasa, M. maximus cv. Supermombasa o Miyagi 2. poorly drained soils with three accessions: U. radicans cv Corner, Urochloa híbrido “Caymán”, U. humidicola Each treatment includes two repetitions (1200 m2 each). Technical support and demonstrations were provided on the implementation of the experiment protocol. The trials were established by The Livestock Association (AGI) and the University Center of Izabal (CUNIZAB). Evaluations were conducted at different intervals and provided insights into the adaptability and performance of various forage cultivars and hybrids under different conditions. A soil analysis, detailed in the report, contributes valuable information for designing sustainable and context-specific interventions. A participatory evaluation was conducted by local farmers. Their insights and experiences contribute to the alignment of interventions with the needs and realities of those directly engaged in livestock production. The challenges encountered during the initiative, including budget constraints and weather-related issues, underscore the complexities of implementing sustainable agricultural practices. The experiment will continue in 2024 when detailed results of agronomic and participatory evaluations, as well as grazing experiments, will be presented.